Microclimate for cultural heritage : measurement, risk assessment, conservation, restoration, and maintenance of indoor and outdoor monuments /: measurement, risk assessment, conservation, restoration, and maintenance of indoor and outdoor monuments. (2019) - Camuffo, Dario
No abstract available